Chronic Intermittent Hypobaric Hypoxia Restores Hippocampus Function and Rescues Cognitive Impairments in Chronic Epileptic Rats via Wnt/β-catenin Signaling - Sun, Can; Fu, Jian; Qu, Zhenzhen; Jia, Lijing; Li, Dongxiao; Zhen, Junli; Wang, Weiping (Frontiers in Molecular Neuroscience, 2021)
Epilepsy is a complex neurological disorder with frequent psychiatric, cognitive, and social comorbidities in addition to recurrent seizures. Cognitive impairment, one of the most common comorbidities, has severe adverse effects on quality of life. Chronic intermittent hypobaric hypoxia (CIHH) has demonstrated neuroprotective efficacy in several neurological disease models. In the present study, we examined the effects of CIHH on cognition and hippocampal function in chronic epileptic rats. CIHH treatment rescued deficits in spatial and object memory, hippocampal neurogenesis, and synaptic plasticity in pilocarpine-treated epileptic rats. The Wnt/ β-catenin pathway has been implicated in neural stem cell proliferation and synapse development, and Wnt/ β-catenin pathway inhibition effectively blocked the neurogenic effects of CIHH. Our findings indicate that CIHH rescues cognitive deficits in epileptic rats via Wnt/ β-catenin pathway activation. This study establishes CIHH and Wnt/ β-catenin pathway regulators as potential treatments for epilepsy- induced cognitive impairments.